Report of the State of the world's plant genetic resources for food and agriculture: prepared for the International Technical Conference on Plant Genetic Resources held at Leipzig, Germany, 17-23 June 1996 - FAO (FAO, 1997)
The main body of the Report provides an assessment of the state of plant genetic resources for food and agriculture and current effectiveness of and capacity for their conservation, development and use. Background data, is porvideed in appendices, as well as in figures and tables following each chapter.